Endogenous growth regulator detection in guinea grass seeds - Usberti, Roberto; Valio, Ivany Ferraz Marques (Pesquisa Agropecuaria Brasileira, 1997)
Endogenous growth regulator activity/level was detected in guinea grass (Panicum maximum Jacq.) seeds, a species widely used as a forage crop in the tropics, aiming at explaining its high seed dormancy level. Seeds were previously scarified or not with sulphuric acid and osmoconditioned on PEG-6000. Endogenous growth regulators were detected as follows: gibberellin-like activity (growth of lettuce hypocotyl bioassay); cytokinins (increase of fresh mass of radish cotyledon bioassay); ABA (spectrophotometer at 230 nm). Exogenous application of GA3 showed a germination increasing effect while ABA had a complete effectiveness to prevent it. High-dormancy seed samples had higher gibberellin-like activity than low-dormancy ones and intact seeds showed higher gibberellin-like activity than scarified seeds; however, after osmoconditioning, opposite results were recorded. No significant activity of neutral promoters and cytokinins was detected. Average levels of ABA for untreated, osmoconditioned after zero- and two-month-storage seed samples were 0.51, 0.39 and 0.21 mg.100 kg-1, respectively. Chemical scarification did not alter either ABA levels in high-dormancy seed samples (0.66 mg.100 kg-1) or those of low-dormancy (0.23 mg.100 kg-1), the former being significantly higher than the latter. Finally, the results show that a gibberellin-ABA interaction appears to be the main factor accounting for dormancy, germination and osmoconditioning control in guinea grass seeds.
Keywords: germination; dormancy; osmoconditioning; Panicum maximum